Dynamique spatio-temporelle des paysages forestiers dans le Sud du Sénégal : cas du département de Vélingara - Boubacar Solly; El Hadji Balla Dieye; Issa Mballo; Oumar Sy; Tidiane Sane; Mamadou Thior (Physio-Géo)
Forest landscapes located of southern Senegal, particularly in the department of Velingara, are increasingly subject to deforestation. As a result, there is a strong tendency to "savanise" them, hence the Senegalese authorities' major concern to take the problem in charge. In such a situation, the study of the spatio-temporal dynamics of the vegetation cover becomes relevant for a sustainable management of the forest resources. This is the purpose of this study which aims to analyze the evolution of the forest landscapes of the department of Velingara and the factors of their dynamics. The methodology adopted is based on the exploitation of Landsat satellite imagery acquired in 1987, 2003 and 2018, and on field work. The results indicate a "savanization" linked to a significant deforestation and a growth of agricultural areas in the north and center of the department. This evolution is all the more marked according to an east-west gradient. Between 1987 and 2003, the forest lost 93642 ha of its area (17 %), against a progression of the savannah (+59717 ha) and cultivation areas (+26380 ha) associated with the zones of habitat and bare grounds. The period 2003-2018 is marked by the regression of the forest and the savannah; 34149 and 6108 ha respectively, to the benefit of a significant increase in agricultural area (+35055 ha) and the habitats (+10466 ha). This dynamic results from the combination of several factors: clearing for agricultural needs, bush fires, population increase, uncontrolled logging, changes in rainfall conditions, among others.